2002
DOI: 10.1080/09500340110105948
|View full text |Cite
|
Sign up to set email alerts
|

Numerical simulation of coherent transport in quantum wires for quantum computing

Abstract: A solid-state implementation of a universal set of gates for quantum computation is proposed and analysed using a time-dependent 2D SchroÈ dinger solver. The qubit is de®ned as the state of an electron propagating along a couple of quantum wires. The wires are suitably coupled through a potential barrier with variable height and/or width. It is shown how a proper design of the system allows the implementation of any one-qubit transformation. The two-qubit gate is realized through a Coulomb coupler able to enta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
38
0

Year Published

2004
2004
2009
2009

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 22 publications
(38 citation statements)
references
References 18 publications
0
38
0
Order By: Relevance
“…The comparison between the SAW assisted and the ballistic transport shows that SAW help the electron to reach the end of the channel without been reflected by the roughness. As seen in [9,10] SAW significantly contribute in keeping the electron wavepacket confined. Figures 3 and 4 clearly show that the wavepacket, in the ballistic case, is destroyed and partially reflected while in the SAW assisted case it reaches the end of the wire essentially unchanged.…”
Section: Single Wirementioning
confidence: 96%
See 1 more Smart Citation
“…The comparison between the SAW assisted and the ballistic transport shows that SAW help the electron to reach the end of the channel without been reflected by the roughness. As seen in [9,10] SAW significantly contribute in keeping the electron wavepacket confined. Figures 3 and 4 clearly show that the wavepacket, in the ballistic case, is destroyed and partially reflected while in the SAW assisted case it reaches the end of the wire essentially unchanged.…”
Section: Single Wirementioning
confidence: 96%
“…It has been suggested the possibility of using SAW as a means to inject and drive electrons along quantum wires [3][4][5][6][7][8]. The group of the authors has shown that SAW can enhance the functionality of coupled ideal quantum wires able to perform the basic operations needed for quantum computing [9][10][11].…”
Section: Introductionmentioning
confidence: 99%
“…Two alternative possibilities have been considered in literature, namely the charge localization of electrons transmitted through a couple of QWRs [8][9][10][11] and the spin orientation of electrons, moving along a single QWR [12,13]. In both cases the theoretical feasibility of a universal set of quantum gates has been demonstrated.…”
Section: Qubits As Electron States In Quantum Wiresmentioning
confidence: 98%
“…[8] and [10], and give the definition of the two states of the qubit, |0 and |1 , in terms of charge localization in two parallel QWRs and of the logical transformations induced by wire coupling. The basic device consists of two parallel QWRs realized, for example, by a GaAs-Al x Ga 1−x As or SiSiO 2 structure [15].…”
Section: Qubits As Electron States In Quantum Wiresmentioning
confidence: 99%
“…To this end, two pairs of QWRs may be brought close to one another so that the electrons in the QWRs can interact with one another in a controlled way via their Coulomb repulsion. This concept has been analyzed both for wave packets 22,23,24,25 as well as for stationary states 20,26,27 . The latter investigations used simple models that provide important proofs-of-principle, but do not provide quantitative predictions of realizable device structures that exhibit quantum gate operations.…”
Section: Introductionmentioning
confidence: 99%